Cenozoic intraplate tectonics in Central Patagonia: Record of main Andean phases in a weak upper plate - Gianni, Guido Martin (2017)
Contraction in intraplate areas is still poorly understood relative to similar deformation at plate margins. In order to contribute to its comprehension, we study the Patagonian broken foreland (PBF) in South America whose evolution remains controversial. Time constraints of tectonic events and structural characterization of this belt are limited. Also, major causes of strain location in this orogen far from the plate margin are enigmatic. To unravel tectonic events, we studied the Cenozoic sedimentary record of the central sector of the Patagonian broken foreland (San Bernardo fold and thrust belt, 44°30′S-46°S) and the Andes (Meseta de Chalia, 46°S) following an approach involving growth-strata detection, U-Pb geochronology and structural modeling. Additionally, we elaborate a high resolution analysis of the effective elastic thickness (Te) to examine the relation between intraplate contraction location and variations in lithospheric strength. The occurrence of Eocene growth-strata (~ 44–40 Ma) suggests that contraction in the Andes and the Patagonian broken foreland was linked to the Incaic phase. Detection of synextensional deposits suggests that the broken foreland collapsed partially during Oligocene to early Miocene. During middle Miocene times, the Quechua contractional phase produced folding of Neogene volcanic rocks and olistostrome deposition at ~ 17 Ma. Finally, the presented Te map shows that intraplate contraction related to Andean phases localized preferentially along weak lithospheric zones (Te < 15 km). Hence, the observed strain distribution in the PBF appears to be controlled by lateral variations in the lithospheric strength. Variations in this parameter could be related to thermo-mechanical weakening produced by intraplate rifting in Paleozoic-Mesozoic times.